The Characteristics Surface Wind Around Soekarno-Hatta Airport Based on Analysis of Frequency Distribution Using Windrose Application - Heri Azhari Noor; Aulia Khamas H; Tutun Juhana; Danang Rimbawa; M. Fachrurrozy (Journal on Education, 2024)
The study of surface wind characteristics in the airport area is needed to support flight operations in terms of safety and economy. Surface wind data is required during the aircraft take-off and landing phases. The information on surface wind characteristics is used for flight operational planning or the construction and expansion of an airport runway. To be able to know the description of the monthly surface wind profile in the airport area, the frequency distribution method is very appropriate to use. Research on surface wind patterns with the frequency distribution method in the Soekarno-Hatta Airport area over the past ten-year period shows that January - April the surface wind direction is dominated from the west, May - September is dominated from the east. The months of October, November, and December are a transition from the east to return to the west which is dominated from the south and southwest. This is in line with the general pattern of Indonesia's climate which is influenced by the west monsoon and east monsoon phenomena.